Upaya Pencegahan Stunting melalui Pengolahan Makanan Berbasis Ikan pada Balita di Pulau Enggano, Kabupaten Bengkulu Utara - Epti Yorita; Dahrizal Dahrizal; Sahidan Sahidan; Mely Gustina; Anang Wahyudi; Zamharira Muslim; Sandy Ardiansyah (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Stunting in Indonesia is still high, including in Bengkulu Province with the locus on the outermost island, namely Meok Village, Enggano District. Stunting events affect the neurological development and cognitive abilities of children. Risk factors for stunting include education. knowledge, protein intake, infection, exclusive breastfeeding, fish food restriction culture. So that efforts are needed to increase the knowledge and ability of the community in processing local fish food ingredients as a food source for toddlers. The purpose of community service activities is to increase the knowledge and skills of mothers with toddlers in processing fish-based local food ingredients as an effort to prevent stunting in toddlers. The activity targets of mothers who have children under five are 35 people. Place of implementation Meok and Apoho Village, Enggano District, North Bengkulu Regency. Activities carried out in September-December 2021. The method of activity is the preparation, implementation, evaluation, follow-up plans. The result is an increase in the average score of knowledge about stunting prevention efforts from 11.09 before the activity to 18 after the activity. Mothers who have children under five are able to process fish-based food ingredients in the form of banana fish porridge and fish rollade. It can be concluded that this community service activity can increase the knowledge and ability of toddler mothers in processing fish-based food. It is suggested to health service providers to empower cadres in health promotion for stunting prevention through processing food menus in accordance with local wisdom.